Hubungan Laju Alir Saliva dengan Performa Mastikasi Berdasarkan Usia pada Pengguna Gigi Tiruan Lengkap: Studi Cross Sectional - Sry Yanti Octavia Simanjuntak; Ismet Danial Nasution; Ranu Putra Armidin (Pusat Riset dan Inovasi Nasional, 2025)
Edentulism is the condition of losing all permanent teeth in the upper and lower jaws, which can impair masticatory function. Masticatory performance is influenced by various factors, one of which is the salivary flow rate, which is also affected by age. This study aimed to determine the average salivary flow rate and masticatory performance, as well as their correlation based on age in complete denture (CD) wearers at the Dental and Oral Hospital of Universitas Sumatera Utara. This research is a descriptive-analytic study with a cross-sectional design involving 20 respondents, consisting of 10 adults (aged 19–59 years) and 10 elderly individuals (aged ≥60 years). The salivary flow rate was measured using the spitting method with sugar-free chewing gum, and masticatory performance was assessed using the color-changeable chewing gum method and the Visual Analog Scale (VAS). Results showed that the average salivary flow rate in adults was 3.18 ± 0.91 ml/min, and in the elderly was 2.29 ± 1.29 ml/min. The average masticatory performance score in adults was 3.8 ± 1.14, and in the elderly was 3.4 ± 1.17. Spearman correlation test showed a significant correlation between salivary flow rate and masticatory performance in both adults (p=0.014) and the elderly (p=0.049). In conclusion, there is a significant relationship between salivary flow rate and masticatory performance based on age. Adult patients demonstrated better salivary flow rates and masticatory performance than elderly patients.